2017
DOI: 10.1116/1.5006783
|View full text |Cite
|
Sign up to set email alerts
|

Atomically dispersed vanadium oxides on multiwalled carbon nanotubes via atomic layer deposition: A multiparameter optimization

Abstract: The focus of the present work is to investigate the bonding characteristics of vanadium oxide species to different oxygen functional groups on multiwalled carbon nanotubes (MWCNT). Atomic layer deposition (ALD) was used to deposit atomically dispersed vanadium oxide species on MWCNT. To generate atomically dispersed vanadium, only one ALD cycle was applied for the deposition of vanadium. The MWCNT functional groups that are involved in the deposition process were identified by thermal analysis and grafting exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…Alternatively, gas-phase deposition techniques such as chemical vapor deposition (CVD) or ALD can be used to graft VO x onto a supporting surface. The feasibility of producing highly dispersed VO x on different substrates by using ALD has been reported previously. Furthermore, catalysts prepared by one of the two methods, impregnation and gas-phase deposition, have already been studied in oxidative dehydrogenation (ODH) reactions of methanol and ethanol regarding structural and catalytic properties. , …”
Section: Introductionmentioning
confidence: 82%
“…Alternatively, gas-phase deposition techniques such as chemical vapor deposition (CVD) or ALD can be used to graft VO x onto a supporting surface. The feasibility of producing highly dispersed VO x on different substrates by using ALD has been reported previously. Furthermore, catalysts prepared by one of the two methods, impregnation and gas-phase deposition, have already been studied in oxidative dehydrogenation (ODH) reactions of methanol and ethanol regarding structural and catalytic properties. , …”
Section: Introductionmentioning
confidence: 82%
“…In selective hydrogenation of 1,3‐butadiene, the catalyst achieved high activity, selectivity and high durability. In recent work, our group used oxidized CNT as a substrate to load vanadium by the ALD method (Figure ) . It was confirmed that the vanadium precursor vanadium‐oxytriisopropoxide not only reacts with phenolic groups, but also forms chemical bonds with carboxylic and anhydride groups.…”
Section: Synthesis Methods For Supported Single Atomsmentioning
confidence: 90%
“…[8][9][10] In another part, carbon is often being used as catalyst support for those metal species to provide good electron transfer ability or to enhance the catalyst dispersity. [11,12] Commercial glassy carbon electrodes are often used to coat with different catalysts to study the performance of the electrocatalysts. In this case, the carbon support is considered to be totally inert to the electrolytes and the applied potentials.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, oxygen‐functionalized carbon materials were used as catalysts for oxidation evolution reaction (OER), in spite of carbon corrosion at oxidative potential [8–10] . In another part, carbon is often being used as catalyst support for those metal species to provide good electron transfer ability or to enhance the catalyst dispersity [11,12] . Commercial glassy carbon electrodes are often used to coat with different catalysts to study the performance of the electrocatalysts.…”
Section: Introductionmentioning
confidence: 99%